Unprofitable agriculture - It is a myth - S. S. Pronin (Овощи России, 2009)
Becoming one of leading region among other ones, Vladimir region located in the central European part of Russia is a place with remarkable geographic and economic conditions including rapid development of communication and traffic system. The territory covers an area of 2908.4 thousand of hectares, where 757 thousand of them are cropping lands including 518.2 thousand of hectares of arable land. 265 agricultural institutions, 2 thousand of farms are involved in agricultural sector. The total gross output and food industry of this oblast reached 20.3% including agriculture 11.8%. 329.7 thousand of inhabitants live in this area, while for the most part of them, 176.3 thousand work for agriculture. The agricultural program of the region is oriented to cattle farming, including extensive milk production. L. P Bakrina is a general manager in one of the largest farming joint stock company "MECHTA" in Murom oblast, Vladimir region. Her farming company that has become renowned as leading among others was rewarded by honoured diploma and awards for high quality products that were highly commended by A.Gordeev, Minister of Agriculture of Russia.